Effect Influencing Factor Toward Brand Loyalty in Online Platform Laundry Service - Febriyan, Aris; Putro, Utomo Sarjono (Proceedings International Conference on Education Innovation and Social Science, 2023)
The laundry industry in Indonesia has been undergoing a significant transformation in recent years, largely driven by the increasing use of social media as a marketing and engagement tool. The massive laundry industry in Indonesia causes entrepreneurs in the laundry sector to face the challenge of securing their customers so they don't switch to using the same services offered by competitors. Therefore, this research was conducted to identify the factors that influence brand loyalty and provide recommendations for development plans to increase brand loyalty which is the object of this study. This study uses quantitative methods, online surveys as instruments and uses PLS-SEM analysis. This study used 151 respondents who are users of laundry services who live in the city of Bandung. This study reveals that Brand Trust has a positive relationship toward Brand Loyalty, Customer Engagement has a positive relationship toward Brand Loyalty, and Relationship Marketing Orientation has a positive relationship toward Brand Loyalty and Customer Engagement. The findings of this study provide recommendations to the company regarding the object of this research to develop development plans and strategies for increasing brand loyalty based on the identified factors that significantly influence brand loyalty which will have an impact on increasing sales.